A study on the evaluation of the quality of Bx7OE wheat varieties - Featherstone , Rachel (My University, 2026)
Improving the end use quality of wheat remains a primary objective for hard winter wheat (HWW) breeders, particularly where bread production is the primary end product. In recent years, one focus has been on the Glu-B1al, which overexpresses the Bx7 glutenin allele, sometimes leading to improvements in dough rheology. While there are numerous studies regarding genetics, molecular characterization, and rheology of wheat lines containing Bx7OE, few have analyzed the baking performance. It has been shown that certain Bx7OE wheats can be significantly stronger than non-overexpressed wheats, while milling extraction, and physical grain characteristics are relatively similar to non-overexpressed varieties. In the existing research regarding the Bx7OE varieties, there is a gap in identifying the appropriate testing methods for the varieties with extreme strength, which surpass standard protocols and current quality targets. The impact of such varieties on end product testing has also been poorly characterized to date. To address these gaps, the following objectives were established for the study. The individual overexpressed varieties were characterized for kernel parameters, experimental milling performance, whole meal and refined flour composition, and dough rheology (GlutoPeak, Farinograph, Alveograph and Mixograph). Blends were created between overexpressed varieties and non-overexpressed base flours in several percentages to assess whether blending could decrease test time while still discriminating quality. Blending was also assessed as a strategy to improve baking quality of base flours, under a standard straight dough method. Finally, a model was developed to determine how the rheological parameters explain the variance of loaf specific volume. The results indicated that the GlutoPeak instrument was able to discriminate quality for both whole meal and refined flours, though more so with refined flour. For the blend of overexpressed and base flours, the results demonstrated that at low levels (5-10%) discrimination was diminished as compared to higher levels and to testing individual flours. Dough rheology testing of refined flours revealed that blending was effective in reducing test time while still allowing discrimination in the quality of rheological parameters, particularly using the Farinograph. Baking revealed that the significant differences seen in rheology did not translate into quality improvements in bread (specific volume range: 3.98-4.57 g/mL). Modeling of rheological parameters for loaf specific volume resulted in only very modest explanatory power (R2=0.139, p<0.001). Based on these results, from a practical perspective, the GlutoPeak testing of both refined and whole meal flour is an appropriate testing method for the Bx7OE lines. The findings presented in this study also suggest that Bx7OE lines can be blended into base flours to improve stability of bread doughs, with no impact on final bread volume. Additionally, both dough rheology and end product quality must be considered together as targets for further wheat quality improvement.
Keywords: Wheat breeding; Glu-B1al; Bx7 overexpression; Dough rheology; Baking quality